Analisis Teknik Audit Berbantuan Komputer dalam Mendeteksi Fraud (Kecurangan) : Sebuah Studi Literatur Review - Ladi Elsa Gita Bualemo; Ainun Arizah (AKUNTANSI 45, 2025)
This study aims to explain how computer-aided audit techniques are applied in detecting fraud. The research employs a literature review approach by examining findings from previous journal articles. Data were gathered through an in-depth review of studies discussing Computer Aided Audit Techniques (CBT) published between 2012 and 2025 in various national journals indexed from SINTA 1 to SINTA 5. The review shows that CBT represents an audit method that integrates information technology to support every stage of the audit process, beginning with planning and continuing through evidence collection, analysis, and final reporting. The use of these tools enhances auditors’ ability to process large volumes of electronic data, identify unusual patterns, and perform more comprehensive testing than traditional manual procedures. The findings indicate that the implementation of CBT significantly strengthens the quality, effectiveness, and efficiency of audit work by accelerating data processing, improving the accuracy of analytical procedures, and increasing the likelihood of detecting irregularities or fraud indicators. Overall, the literature confirms that CBT plays an essential role in modern auditing practices and serves as a valuable instrument for improving fraud detection in increasingly digitalized organizational environments.